PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT SWASTA DI KOTA BATAM - Wasiman, Wasiman (EDUTECH CONSULTANT, 2018)
This study aims to determine the influence of leadership style, motivation and communication on employee performance at private hospitals in Batam City. This study used questionnaires distributed to employees of private hospitals in Batam City by distributing questionnaires 200 respondents. This study uses the level of individual analysis. The object of research is the employees of private hospitals in Batam City. This study uses multiple linear regression test which includes the validity, reliability, normality, and r square test. The results showed that the coefficient of determination (R2) has a value of 0.740 which means that the variable of employee performance variable can be explained by the variable of leadership style, motivation and communication equal to 74,%, while the rest is 26,% influenced by factors that do not exist in research this.